Analysis Of The Role Of Facilitators In Increase Customers' Business Income In PT. Bank BTPN Syariah Tbk. In Besitang - Rambe, Siti Nurhaliza; Rangkuti, Sahnan; Firah, Al (Universitas Dharmawangsa Medan, 2025)
This study aims to determine how the role of facilitator assistants in increasing the income of umkm customers at PT Bank BTPN Syari`ah, what are the obstacles to the role of facilitator assistants in increasing the income of umkm customers at PT Bank BTPN Syari`ah, and what solutions can overcome the obstacles experienced by facilitator assistants in increasing the income of umkm customers at PT Bank BTPN Syari`ah. The type of data used in this research is qualitative data. Data collection methods using interviews and documentation. The informants used in the study were 8 people who were part of the company, namely senior business manager, business manager, community officer, mentor, facilitator and customer. The results of this study indicate that the role of the facilitator of PT Bank BTPN Syari'ah in Besitang is quite good, but not yet maximized as a whole. There are still obstacles that occur in the mentoring process, one of which is limited resources, limited abilities and knowledge, limited budget and others. In facing these obstacles, a solution is needed so that the assisting facilitator can process well in assisting the business of PT Bank BTPN Syari'ah customers in Besitang. Solutions that can be done to overcome these obstacles include improving the skills and knowledge of facilitator assistants, applying for a budget to the company to help smooth the mentoring process and other solutions.